Modelling Upholstered Furniture Frames Using the Finite Element Method - Łukasz Matwiej; Krzysztof Wiaderek; Witold Jarecki; Dariusz Orlikowski; Marek Wieruszewski (Applied Sciences)
This study employs the finite element method to propose a model-based design strategy for upholstered furniture frames. Three-dimensional discrete models of these frames were created, considering the orthotropic characteristics of pine (Pinus sylvestris L.) and spruce (Picea abies L.) wood, reinforced structurally with glue joints and upholstery staples. The modelling process utilised the CAE system Autodesk Inventor Nastran, applying the finite element method (FEM). Static analyses were performed by simulating standard loading conditions. The calculations incorporated the stiffness coefficients of the frame’s comb joint connections. The findings illustrate the stress distribution, displacements, and equivalent strains within the furniture frame models. The deformation and strength parameters of the frames introduce a novel perspective on designing upholstered furniture structures using the component-based FEM approach. These outcomes are applicable to the development of upholstered furniture designs.